A review of clinical aspects of breast cancer. (February 2014) - Libson, Shai; Lippman, Marc
Abstract Breast cancer is the most frequently diagnosed cancer in women and ranks second among causes for cancer related death in women. The ability to identify and diagnose breast cancer has improved markedly. Treatment decisions which were based in the past predominantly on the anatomic extent of the disease are shifting to the underlying biological mechanisms. Gene array technology has led to the recognition that breast cancer is a heterogeneous disease composed of different biological subtypes, and genetic profiling enables response to chemotherapy to be predicted. Breast conservation became an established standard of care and the oncoplastic approach enables wide excisions without compromising the natural shape of the breast. Sentinel lymph node biopsy has replaced axillary dissection as the standard procedure to stage the axilla and spared many patients the excess morbidity of axillary dissection. Targeted therapy to the oestrogen receptor plays a major role in systemic therapy; pathways responsible for endocrine resistance have been targeted as well. Biological therapy has been developed to target HER2 receptor and combination of antibody drug conjugates linked cytotoxic therapy to HER2 antibodies. Meaningful improvements in survival resulted from the new effective systemic agents and patients with metastasis are likely to have a longer survival.